PENGARUH ELECTRONIC WORD OF MOUTH, CITRA MEREK DAN KEPERCAYAAN TERHADAP KEPUTUSAN PEMBELIAN DI MATAHARI - Diana Leli Indratno; Lalu Supardin; Eka Wiranto (JURNAL ILMIAH EDUNOMIKA, 2021)
This study aims to determine the effect of Electronic Word Of Mouth, Brand Image and Trust on Purchase Decisions at Matahari and at the same time find out how much contribution is given by Electronic Word Of Mouth, Brand Image and Trust to Purchase Decisions at Matahari. The population in this study is solar consumers in Yogyakarta with a total sample of 100 respondents. This study used primary and secondary data, the type of research used is a quantitative research type, while the tool used is a questionnaire. The data analysis methods used to answer this research problem are: (1) Qualitative Analysis which includes the characteristics of the respondents (2) Test of the research instrument which includes validity and reliability tests (3) Quantitative analysis which includes multiple linear regression analysis and hypothesis testing which includes test t, f test and R2 test (determination). The results showed that the contribution given by Electronic Word Of Mouth (X1), Brand Image (X2) and Trust (X3) to Purchase Decisions (Y) is 65.50% while the remaining 34.50% influenced by other variables not examined in this study. Keywords : Electronic Word Of Mouth, Brand Image, and Belief in Purchase Decision